ENT 530 Social Media Portfolio: Snow Oat-Reo / Fatin Alea Md Isa - Md Isa, Fatin Alea (2021)
The summary from this social media portfolio is to focus on how individual manage their imaginary business through online platform. The Snow Oat-Reo business is related to innovation idea of coated the Oreo with blended flours and fry without changing the original taste of Oreo biscuits. The founder wants to try something new and different to attract customer. We choose Oreo as our new product because Oreo cookies replaced the trans-fat in the cookie with nonhydrogenated vegetable oil. Our target participant of our product is among the kids, teenagers, busy people and especially the Oreo lovers. The business also targeting someone who are social media users and love the unique taste of fried Oreo. The business is located at Ampang, Kuala Lumpur. Moreover, it offers two types of fried Oreo flavours which are original and red velvet, and various toppings to be add on. The business operates daily from 12pm to 6pm except for Wednesday. In addition, this business has three workers. The price range is different due to the toppings. As we perform this subject, social media is more likely to reach customer quickly. Lastly, the main operations of the company are making the product, make promotion, selling and marketing. For promotion, we divided into two parts which are hard selling and soft selling. In addition, advertisement is one of the crucial key resources in a business.